Do we intervene inappropriately for ST elevation?. Issue 2 (26th January 2006) - Sanders, A; Froude, A; Probst, F
Abstract : ST elevation on a 12 lead ECG is one of the cardinal features of acute myocardial infarction (AMI), yet it also occurs with other clinical conditions such as spontaneous pneumothorax. Three cases are presented, all of whom had chest pain and ST elevation. All had pneumothoraces yet only one had an AMI. Thrombolysis was administered to one patient. With the current pressure on "door-to-needle" times, emergency physicians should take care to differentiate between these entities.